Graphitic Petal Electrodes for All‐Solid‐State Flexible Supercapacitors. Issue 3 (23rd September 2013) - Xiong, Guoping; Meng, Chuizhou; Reifenberger, Ronald G.; Irazoqui, Pedro P.; Fisher, Timothy S.
<x xml:space="preserve">Abstract</x> The charge storage characteristics of a composite nanoarchitecture with a highly functional 3D morphology are reported. The electrodes are formed by the electropolymerization of aniline monomers into a nanometer‐thick polyaniline (PANI) film that conformally coats graphitic petals (GPs) grown by microwave plasma chemical vapor deposition (MPCVD) on conductive carbon cloth (CC). The hybrid CC/GPs/PANI electrodes yield results near the theoretical maximum capacitance for PANI of 2000 F g−1 (based on PANI mass) and a large area‐normalized specific capacitance of ≈2.6 F cm−2 (equivalent to a volumetric capacitance of ≈230 F cm−3) at a low current density of 1 A g−1 (based on PANI mass). The specific capacitances remain above 1200 F g−1 (based on PANI mass) for currents up to 100 A g−1 with correspondingly high area‐normalized values. The hybrid electrodes also exhibit a high rate capability with an energy density of 110 Wh kg−1 and a maximum power density of 265 kW kg−1 at a current density of 100 A g−1. Long‐term cyclic stability is good (≈7% loss of initial capacitance after 2000 cycles), with coulombic efficiencies >99%. Moreover, prototype all‐solid‐state flexible supercapacitors fabricated from these hybrid electrodes exhibit excellent energy storage performance.